Session-aware popularity-based resource allocation for assureddifferentiated services. - Mendes, P. (IEEE Communications magazine)
Differentiated services networks are fair in the way that different types of traffic can be associated to different network services, and so to different quality levels. However, fairness among flows sharing the same service, may, not be provided. Our goal is to study fairness between scalable multimedia sessions for assured DS services in a multicast network environment. To achieve this goal, we present a fairness mechanism called session-aware popularity-based resource allocation (SAPRA), which allocates resources to scalable. sessions based on their number of receivers. Simulation results in a scalable and multireceiver scenario show that SAPRA maximizes the utilization, of bandwidth and the number of receivers with high-quality reception